On the Semiannual Formation of Large Scale Three‐Dimensional Vortices at the Stratopause. Issue 4 (16th February 2021) - O'Kane, Terence J.; Kitsios, Vassili; Collier, Mark A.
Abstract: An examination of the dynamics of the middle atmosphere as reconstructed in the NASA Modern‐Era Retrospective analysis for Research and Applications, Version 2 (MERRA‐2) reveals the formation of large scale three‐dimensional (3D) vortices in the tropical stratosphere following both the vernal and autumnal equinoxes at times when the jet associated with the westerly phase of the semiannual oscillation (SAO) is maximal and extratropical influences from planetary waves are weakest. An empirical orthogonal function (EOF) analysis of the second matrix invariant of the velocity gradient tensor applied to the shear zones about the SAO reveals statistically stationary wave‐5 vortex structures that span more than 3, 200 km in length and up to 40 km in the vertical. Eliassen‐Palm fluxes suggests the vortices are maintained by a combination of local (shear zones) and remote (vertically propagating tropical) sources of momentum. These large‐scale coherent features appear to be unique to the stratopause. Plain Language Summary: Application of methods commonly employed in engineering fluid mechanics to visualize vortices are used to examine a recent state of the art reconstruction of the middle atmosphere. This analysis reveals huge vortical structures present during the equinoctial seasons in the region of the tropical stratopause. These semiannual coherent features appear to be unique to the middle atmosphere spanning up to 30° longitude at ±15° latitude corresponding to around 3, 200 km in length and between 10 hPa and 0.1 hPa encompassing up to 40 km in the vertical. Key Points: Empirical orthogonal function (EOF) analysis of the second matrix invariant of the velocity gradient tensor is applied to the shear zones about the tropical stratosphere We identify large scale vortices near the tropical stratopause as reconstructed in the NASA MERRA‐2 atmospheric reanalysis The vortices form following the vernal and autumnal equinoxes at times when the westerly jet is maximal